2020
DOI: 10.1098/rsta.2019.0196
|View full text |Cite
|
Sign up to set email alerts
|

Weak invariants in dissipative systems: action principle and Noether charge for kinetic theory

Abstract: In non-equilibrium classical thermostatistics, the state of a system may be described by not only dynamical/thermodynamical variables but also a kinetic distribution function. This ‘double structure’ bears some analogy with that in quantum thermodynamics, where both dynamical variables and the Hilbert space are involved. Recently, the concept of weak invariants has repeatedly been discussed in the context of quantum thermodynamics. A weak invariant is defined in such a way that its value changes in tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…In recent work [ 26 ], the action principle has been formulated for a quantum master equation based on the auxiliary field formalism [ 27 ], and it has been found that the auxiliary field is actually a weak invariant. In addition, the auxiliary field has also shown to be the Noether charge [ 28 ]. This reminds one of another observation: the black hole entropy related to surface gravity can be regarded as the Noether charge [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent work [ 26 ], the action principle has been formulated for a quantum master equation based on the auxiliary field formalism [ 27 ], and it has been found that the auxiliary field is actually a weak invariant. In addition, the auxiliary field has also shown to be the Noether charge [ 28 ]. This reminds one of another observation: the black hole entropy related to surface gravity can be regarded as the Noether charge [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The third benchmark, backward compatibility, should precede the mathematical structure. The compatibility with a statistical treatment, based on a given microscopic or mesoscopic material composition, is a clear benchmark of any general phenomenology and appears here in the papers [1,10,12]. In particular, the compatibility with the kinetic theory is important in [3,[6][7][8].…”
Section: The Necessary Benchmarksmentioning
confidence: 98%
“…The usual approach attempts to extend the validity of variational principles to dissipative evolution [13]. In [12], we see a promising new method. On the other hand, GENERIC (General Equation for the Nonequilibrium Reversible-Irreversible Coupling) treats the dissipative-nondissipative parts on equal footing [3,7].…”
Section: The Necessary Benchmarksmentioning
confidence: 99%
“…are not symmetric; therefore, special modifications are necessary to construct a variational principle in order to circumvent the strict mathematical conditions [3][4][5]. The applied tricks can be very different: for instance, changing the original equations, increasing the number of variables, reducing the corresponding function spaces, turning to statistical interpretations, and so on [6][7][8][9][10][11][12][13]. The obtained variational principles are special, different and not equivalent [14].…”
Section: Variational Principles For Dissipative Processesmentioning
confidence: 99%
“…The applied tricks can be very different: for instance, changing the original equations, increasing the number of variables, reducing the corresponding function spaces, turning to statistical interpretations, and so on [6][7][8][9][10][11][12][13]. The obtained variational principles are special, different and not equivalent [14].…”
Section: Variational Principles For Dissipative Processesmentioning
confidence: 99%